Prefrontal-inferotemporal interaction is not always necessary for reversal learning. - Wilson, C; Gaffan, D (2008)
Prefrontal cortex (PFC) is thought to have a wide-ranging role in cognition, often described as executive function or behavioral inhibition. A specific example of such a role is the inhibition of representations in more posterior regions of cortex in a "top-down" manner, a function thought to be tested by reversal learning tasks. The direct action of PFC on posterior regions can be directly tested by disconnecting PFC from the region in question. We tested whether PFC directly inhibits visual object representations in inferotemporal cortex (IT) during reversal learning by studying the effect, in macaque monkeys, of disconnecting PFC from IT by crossed unilateral ablations. We tested two visual object reversal learning tasks, namely serial and concurrent reversal learning. We found that the disconnection severely impairs serial reversal learning but leaves concurrent reversal learning completely intact. Thus, PFC cannot be said to always have direct inhibitory control over visual object representations in reversal learning. Furthermore, our results cannot be explained by generalized theories of PFC function such as executive function and behavioral inhibition, because those theories do not make predictions that differentiate different forms of reversal learning. The results do, however, support our proposal, based on other experimental evidence from macaque monkeys, that PFC has a highly specific role in the representation of temporally complex events.